Application of the continuous wavelet transform on seismic data for mapping of channel deposits and gas detection at the CO2 SINK site, Ketzin, Germany - Kazemeini, S.; Juhlin, Christopher; Zinck-Jørgensen, K.; Norden, B. (Wiley-Blackwell, 2009)
Conventional seismic data are band limited and therefore, provide limited geological information. Every method that can push the limits is desirable for seismic data analysis. Recently, time-frequency decomposition methods are being used to quickly extract geological information from seismic data and, especially, for revealing frequency-dependent amplitude anomalies. Higher frequency resolution at lower frequencies and higher temporal resolution at higher frequencies are the objectives for different time-frequency decomposition methods. Continuous wavelet transform techniques, which are the same as narrow-band spectral analysis methods, provide frequency spectra with high temporal resolution without the windowing process associated with other techniques. Therefore, this technique can be used for analysing geological information associated with low and high frequencies that normally cannot be observed in conventional seismic data. In particular, the continuous wavelet transform is being used to detect thin sand bodies and also as a direct hydrocarbon indicator. This paper presents an application of the continuous wavelet transform method for the mapping of potential channel deposits, as well as remnant natural gas detection by mapping low-frequency anomalies associated with the gas. The study was carried out at the experimental CO2 storage site at Ketzin, Germany (CO2 SINK). Given that reservoir heterogeneity and faulting will have significant impact on the movement and storage of the injected CO2, our results are encouraging for monitoring the migration of CO2 at the site. Our study confirms the efficiency of the continuous wavelet transform decomposition method for the detection of frequency-dependent anomalies that may be due to gas migration during and after the injection phase and in this way, it can be used for real-time monitoring of the injected CO2 from both surface and borehole seismics. © 2009 European Association of Geoscientists & Engineers.